Universal basic income and the threat to democracy as we know it - Nelson, Peter (Economics collection, 2018)
1. Introduction -- 2. The future of employment -- 3. Progression of disappearing jobs -- 4. Prospects for new jobs -- 5. Climate change -- 6. Universal or unconditional basic income -- 7. Benefits of a UBI -- 8. Shortcomings of a UBI -- 9. Gender divide -- 10. What will need to change -- 11. Funding -- 12. Legal framework -- 13. What people do without jobs -- 14. Structural fluidity -- 15. Democracy as it is understood --16. The other side of democracy -- 17. Evolving political framework -- 18. Adjusting to change -- 19. Military intervention -- 20. Time frame -- 21. Will democracy survive? -- 22. What can be done for democracy to survive -- 23. Remaining questions -- About the author -- Index